INCREASING STUDENT’S UNDERSTANDING ABILITY AND MATHEMATICAL REASONING AND LEARNING MOTIVATION OF JUNIOR HIGH SCHOOL STUDENTS USING DISCOVERY LEARNING METHOD - Juhanah, Ida; Sabandar, Jozua (IKIP SILIWANGI, 2018)
This research aims to examine the improvement of understanding ability and mathematical reasoning as well as the motivation of learning of junior high school students by discovery learning method conventional method. In addition, it aims to check the improvement of understanding ability and mathematical reasoning as well as the motivation of learning though junior high school students. This research was quasi experiment which was designed to nonequivalent control group. The study The population on this research was all the junior high school students of Cipeundeuy 2 Junior High School West Bandung Regency. The Sample was two classes of 7th grade students. The data was attained by understanding thinking and mathematical test which using material of algebraic form and questionnaire motivation to learn